Motywacja i moralność łowiecka - Elżanowski, Andrzej (Zoophilologica. Polish Journal of Animal Studies, 2018)
There is a growing public disapproval of the recreational persecution and killing of wild mammals and birds who share with us basic emotional experience that conveys intrinsic value to their lives. Contrary to hunters’ propaganda, both scientific research and testimonies from prominent hunters-writers demonstrate that the thrill of killing is the main and ultimate motive of recreational hunting. The majority of simple-minded hunters are satisfied by any killing, including a canned hunt. However, some recreational hunters combine the killing drive with biophilia which makes them psychologically comparable to rapists. Both the thrill of killing and biophilia are primitive drives that evolved as adaptations in hunter-gatherers. Killing for pleasure (with or without biophilia) has always been evil in terms of both intentions and consequences. At present it is also barbaric in the sense of the opposite of civilization which progressed by increasing the control of primitive drives, in particular aggression.